2021
DOI: 10.1021/acs.inorgchem.0c03765
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Synthesis of Uranyl Vanadate Nanoshell Heteropolyoxometalates

Abstract: Two uranyl vanadate heteropolyoxometalates (h-POMs) have been synthesized by ionothermal methods using the ionic liquid 1ethyl-3-methylimidazolium diethyl phosphate (EMIm-Et 2 PO 4 ). The hybrid actinide−transition metal shell structures have cores of (UO 2 ) 8 (V 6 O 22 ) and (UO 2 ) 6 (V 3 O 12 ), which we designate as {U 8 V 6 } and {U 6 V 3 }, respectively. The diethyl phosphate anions of the ionic liquids in some cases terminate the core structures to form actinyl oxide clusters, and in other cases the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…19). 118 {U 8 V 6 } and {U 6 V 3 } could be obtained with different extended structures from an ionic liquid solution containing 1-ethyl-3-methylimidazolium diethyl phosphate (EMIm-Et 2 PO 4 ), UO 2 (NO 3 ) 2 , NaVO 3 , and/or VOSO 4 , and Na 2 WO 4 . The monomer, dimer, and 1D chain of {U 8 V 6 } and 1D chain of {U 6 V 3 } represent a new series of U-oxo-clusters incorporating vanadium atoms.…”
Section: Synthesis and Structure Of U-pomsmentioning
confidence: 99%
“…19). 118 {U 8 V 6 } and {U 6 V 3 } could be obtained with different extended structures from an ionic liquid solution containing 1-ethyl-3-methylimidazolium diethyl phosphate (EMIm-Et 2 PO 4 ), UO 2 (NO 3 ) 2 , NaVO 3 , and/or VOSO 4 , and Na 2 WO 4 . The monomer, dimer, and 1D chain of {U 8 V 6 } and 1D chain of {U 6 V 3 } represent a new series of U-oxo-clusters incorporating vanadium atoms.…”
Section: Synthesis and Structure Of U-pomsmentioning
confidence: 99%
“…Due to their ready availability, the ILs used to synthesize uranyl compounds are largely imidazolium based. Earlier studies have produced monomeric and dimeric structures built from uranyl ions, chains and sheets, isolated clusters, ,, and a few metal–organic frameworks . Existing methods use complex mixtures of ligands or additional metals in combination with the IL and uranium, which renders the predictability of starting material and product solubility challenging .…”
Section: Introductionmentioning
confidence: 99%
“…The three compounds (mentioned above), reported by Kim and Pope, belong to U-hetero-POMs. Several research groups across the globe have reported U-heterosystems with diverse POMs. Zheng and Kong and their research groups, in 2021, systematically investigated the temperature-dependent photoluminescence studies of an uranium-containing polyoxometalate “Na@U 6 P 6 ” having a sandwich-like structure . In the recent past, the U-heterosilico-/phospho-tungstate systems have been employed as catalysts for organic syntheses. , On the other hand, the uranium-oxo-clusters are primarily self-assembled uranium-oxo-clusters/uranyl peroxide clusters with a number of uranium in these clusters ranging from U 16 to U 124 including their possible hybrids .…”
Section: Introductionmentioning
confidence: 99%